Origin of the Enhanced Reusability and Electron Transfer of the Carbon-Coated Mn3O4 Nanocube for Persulfate Activation - Liu, Yani; Luo, Jun; Tang, Lin; Feng, Chengyang; Wang, Jiajia; Deng, Yaocheng; Liu, Haoyu; Yu, Jiangfang; Feng, Haopeng; Wang, Jingjing (ACS catalysis, 2020)
Manganese oxides and carbon materials are both desirable catalysts for persulfate (PS) advanced oxidation processes in environmental remediation. Nevertheless, manganese oxides suffer from low reusability while carbon materials face the problem of limited catalytic efficiency. For the purpose of making full use of the advantages of the two materials as well as avoiding their shortcomings, carbon-coated Mn3O4 composites (Mn3O4/C) with a regular nanocube structure were designed to activate PS for the removal of organics, and the catalytic processes were deeply investigated. The catalyst prepared at 400 °C with a precursor ratio (glucose/KMnO4) of 0.5 exhibited the best catalytic performance along with satisfactory reusability owing to the protection of the outer carbon layer. According to experimental results and density functional theory calculation, there were van der Waals interaction and a part of the strong attraction between the interface of PS and Mn3O4/C, which could be enhanced by inner Mn3O4 and thus promoted the electron transfer between PS and carbon shell, and the defective edges of the carbon layer with hydroxyl (C–OH) groups could act as active sites for PS activation. Radical (SO4 •–, •OH) and nonradical (1O2) oxidation processes both participated in the degradation of 2,4-dichlorophenol, in which •OH was dominating. This study not only proposed a promising catalyst for the degradation of pollutants but also expanded research ideas for future PS activation mechanism studies by integrating the experiment and simulation.